Perlindungan Hukum Ketenagakerjaan Bagi Dokter Dalam Hubungan Kerja Dengan Rumah Sakit - Mahayani, Brigita Mirna; Aji, Rihantoro Bayu; Ismono, Joko (Law and Humanity, 2023)
According to the existing legal relationship, there are three groups of doctors working in hospitals, namely doctors with the status of permanent employees (PNS), doctors with contract status and visiting doctors (attending physician). There is a shortage of permanent doctors, in general private hospitals employ civil servant doctors who work in government hospitals as visiting doctors. Research objectives: To find out and analyze the regulation of the medical profession based on the positive law in force in Indonesia and to find out and analyze the labor law protection for doctors in working relations with hospitals. The type of research used is formative juridical, the research approach used is a statute approach and a conceptual approach. Labor law protection for doctors in working relationships with hospitals is regulated in the work agreement. The work agreement is an entry point for the norms of labor law protection for doctors who are bound by a working relationship with a hospital. The working relationship between doctors and hospitals was born from a work agreement. The work agreement stipulates the rights and obligations of each party signing the work agreement. Work agreements between doctors and hospitals are an autonomous source of law in work relations. The work agreement will be a source of law to be considered in the event of a dispute over work relations between a doctor and a hospital, in addition to the applicable labor laws and regulations.